A study on the Importance of Learning Mother Tongue in School Curriculum - Dr. Sini. V; Dr.Anil Kumar; Dr.Muhammed Anas (Revista Electronica de Veterinaria, 2024)
Mother tongue is the first language or native language of a person. This is the language we learn at home. Learning of mother tongue through formal education is important because it helps to understood cultural heritage moral values. Learning of mother tongue is essential in school curriculum only through this the child can develop proper communication skill and vocabulary